A case series on survivors of paraquat poisoning complicated by acute kidney injury and acute lung injury - Mondal, Debasis; Bhunia, Prantick Kumar (Indian Journal of Case Reports, 2024)
Paraquat poisoning is nearly fatal. Death occurs by respiratory involvement. It has no antidote and also treatment protocol is lacking. Here, we present a case series of two survivors of paraquat poison who survived after proper care. Both of them were young and ingested in small quantities. Both of them had acute kidney and lung injuries. Patient 2 had an additional liver injury. Here, we have gathered some already published documents on treatment and outcome with a brief review.